Alhagi maurorum extract in combination with lytic phage cocktails: a promising therapeutic approach against biofilms of multi-drug resistant P. mirabilis - Mirzaei, Arezoo; Esfahani, Bahram Nasr; Ghanadian, Mustafa; Wagemans, Jeroen; Lavigne, Rob; Moghim, Sharareh (Frontiers in Pharmacology, 2024)
Antimicrobial resistance (AMR) poses a significant global threat to public health systems, rendering antibiotics ineffective in treating infectious diseases. Combined use of bio compounds, including bacteriophages and plant extracts, is an attractive approach to controlling antibiotic resistance. In this study, the combination of phage cocktail (Isf-Pm1 and Isf-Pm2) and Alhagi maurorum crude extract (AME) was investigated in controlling biofilm-forming multi-drug resistant P. mirabilis isolates, in vitro and a phantom bladder model. The combination of AME and phage cocktails demonstrated no significant disparity in its ability to inhibit quorum sensing (QS) when compared to the individual control of AME alone. Following treatment with the combination of phage cocktail and AME at a 125 μg/mL concentration, the MDR P. mirabilis biofilm biomass was notably reduced by 73% compared to the control (P< 0.0001). The anti-biofilm effect was confirmed by Scanning Electron Microscopy (SEM). Moreover, in a bladder phantom model, there was a considerable decrease in encrustation levels compared to the control. The combined treatment resulted in a 1.85 logarithmic reduction in bacterial adhesion to Vero cells compared to the control. The real-time PCR results indicated significant downregulation of QS- and adhesion-related gens. The phage therapy, combined with AME, holds promising potential in reducing biofilm formation.